Do Sub-syndromal Manic Symptoms Influence Outcome in Treatment Resistant Depression in Adolescents? A Latent Class Analysis from the TORDIA study - Maalouf, Fadi T. (2012)
BACKGROUND: To identify distinct depressive symptom trajectories in the TORDIA study and determine their correlates. METHODS: Latent Class Growth Analysis (LCGA) using the Children's Depression Rating Scale—Revised (CDRS-R) through 72 weeks from intake. RESULTS: 3 classes were identified: (1) little change in symptomatic status (“NO”), comprising 24.9% of participants, with a 72-week remission rate of 25.3%; (2) slow, steady improvement (“SLOW”), comprising 47.9% of participants, with a remission rate of 60.0%, and (3) rapid symptom response (“GO”), comprising 27.2% of participants, with a remission rate of 85.7%. Higher baseline CDRS-R (p<0.001) and poorer functioning (p=0.03) were the strongest discriminators between NO and GO. Higher baseline CDRS (p<0.001) and scores on the Mania Rating Scale (MRS) (p=0.01) were the strongest discriminators between SLOW and GO. Other variables differentiating GO from both NO and from SLOW, were better baseline functioning, lower hopelessness, and lower family conflict. Both NO and SLOW showed increases on the MRS over time compared to GO (ps≤0.04), and increasing MRS was strongly associated with lack of remission by 72 weeks (p=0.02). LIMITATIONS: High rate of open treatment by the end of the follow-up period creates difficulty in drawing clear inferences about the long-term impact of initial randomization. CONCLUSION: Along with depressive severity, sub-syndromal manic symptoms, at baseline, and over time emerged as important predictors and correlates of poor outcome in this sample. Further research is needed on the treatment of severe depression, and on the assessment and management of sub-syndromal manic symptoms in treatment resistant depression.